Efeito par/ímpar da cadeia alquílica catiônica do cloreto de 1-alquil-3-metilimidazólio, [CnC1im]Cl, na formação de sistemas aquosos bifásicos - Belchior, Diana Cléssia Vieira (Universidade Federal do Tocantins, 2017)
Aqueous biphasic systems (ABS) based on ionic liquids (ILs) have been considered as promising liquid-liquid extraction platforms, partcularly when compared with the most typical polymer-based ABS. However, before their application, it is crucial to understand the main mechanisms controling the formation of IL-based ABS. In this study, the influence of the carbon number and odd/even effect of the alkyl side chain length in 1-alkyl-3-methylimidazolium chloride ILs ([CnC1im]Cl, n = 2-12) was comprehensively investigated regarding the formation of IL-based ABS. To this end, the ternary phase diagrams and respective tie-lines of systems composed of [CnC1im]Cl, water and salt (K3PO4 or K2CO3) were determined at 298 K. Furthermore, the Setschenow coefficients, a quantitative measure of the two-phases forming ability, were calculated for each system. The ability of the ILs with long alkyl chain (n> 6) to self-aggregate was also studied in order to understand their impact on the ABS formation. The results obtained reveal two distinct trends for systems composed of ILs, and thus of a odd/even effect reagrding the carbon number in the cation’ alkyl side chain with K2CO3. However, this behavior was not observed in systems formed by K3PO4, maybe du to its strong salting-out capacity which can mask this effect.